Assessment of Hand Function as a Tool for Planning a Rehabilitation Program in Scleroderma Patient a Case Report - Nugroho, Virginia Ainurridlo; Ridwan, Muhammad; Rahmad, Rahmad (Writing Center IMERI FMUI, 2022)
Scleroderma causes reduced versatility and the snugness of the skin due to cutaneous thickening and solidification (sclerosis). Scleroderma affects productivity, particularly hand-related work. A 29 years old man with scleroderma presented pain, contracture of his wrists and fingers, sclerodactyly, hardened skin, tightness, as well as shiny and dry skin. These manifestations decrease hand function, resulting in difficulty doing ADL and his job as a porter. Scleroderma was diagnosed one month prior. The planned treatments are TENS to decrease the pain, USD and hand exercise to increase ROM, Mc mennel and connective tissue massage, home exercise, vocational modification and occupational therapy to maximize the hand function and ADL, and psychotherapy to increase his self-confidence. MHOQ and HAMIS are used to Monitor and evaluate hand function. The assessment before therapy are right side HAMIS : 12; left side HAMIS : 11; VAS : 4; MHQ (Hand function 35% ; ADL 60%; work 30%; Pain 90%; aesthetic 55%; satisfaction 45%) . After 2 month, right side HAMIS : 10; left side HAMIS : 10; VAS : 1 ; MHQ (Hand function 45% ; ADL 72%; work 40%; Pain 40%; aesthetic 55%; satisfaction 70%). HAMIS and MHOQ in scleroderma patients could be used as an accurate assessment tool for planning rehabilitation treatment. The questionnaires can be used as guidelines for modifying the appropriate assistive device for ADL and patient work.